Visible-Light-Mediated Photoredox Reactions in the Total Synthesis of Natural Products - Mateus-Ruiz, Jeferson B.; Cordero-Vargas, Alejandro (Synthesis, 2020)
In the last two decades, the field of photoredox catalysis (PRC) has grown impressively with reports of new synthetic methodologies and more efficient versions of known free-radical reactions. The impressive success of visible-light-mediated photoredox catalysis is, in great part, due to its low environmental impact, mild reaction conditions, clean reactions, and inexpensive methodologies. These features have allowed photoredox catalysis to emerge as a powerful tool in the synthesis of natural products; much excellent work was reported between 2011 and 2015. Since 2016, a number of more efficient and impressive total syntheses of natural products featuring photoredox catalysis have been reported. In this review, we summarize the recent synthetic applications of photoredox catalysis in the total synthesis of natural products between 2016 and 2020.1 Introduction2 Intermolecular Additions from Functionalized Substrates2.1 Intermolecular Additions from Alkyl Halides2.2 Intermolecular Additions from Alcohols and Carboxylic Acids3 Cyclizations from Functionalized Substrates3.1 Cyclizations of Carbon-Centered Radicals3.2 Cyclizations of Nitrogen-Centered Radicals4 Intramolecular Cyclization from Non-functionalized N–H Bonds4.1 Type I Radical Cascade4.2 Type II Radical Cascade4.3 Type III Radical Cascade5 Functionalization of Imines and Enamines6 Cycloadditions7 Miscellaneous7.1 Dehalogenation and Reductive Decarboxylation7.2 Thiyl Radical Promoted Cascade8 Conclusions and Perspectives
Keywords: photoredox catalysis; natural products; addition; cyclization; decarboxylation; dehalogenation; cycloaddition